(untitled) (African Journal of Biomedical Research, 2021)
The burden of hyperlipidemia is on the rise globally especially in many low-income countries like Uganda. Management of this metabolic disorder mainly involves dietary and behavioral therapies, which are often met with poor results as they require time and discipline from the patients. The chemotherapeutic options available are expensive, have many side effects and are rarely available to the average citizen. Thus, an alternative effective remedy which is readily available and cheap is needed to combat the problem of hyperlipidemia. This study sought to establish the effect of the mixture of Allium cepa extract and Camellia sinensis extract on the serum lipid profile of the male wistar rats. Allium cepa and Camellia sinensis mixture in a ratio of 3:7 had the highest antioxidant activity. It reduced body weight, total cholesterol, triacylglycerides, LDL-cholesterol and increased HDL, and in addition it had no toxicity to the liver of the animal models used. It has thus been recommended as a potential therapy for hyperlipidemia and its associated complication of liver toxicity. A pharmaco-kinetic study regarding the interaction of antioxidants for combinations of Allium cepa and Camellia sinensis extracts in different ratios should be conducted to understand the cause of synergism and antagonism.